2021
DOI: 10.1038/s41467-021-26185-z
|View full text |Cite
|
Sign up to set email alerts
|

The geography of intergenerational social mobility in Britain

Abstract: Empirical analysis of social mobility is typically framed by outcomes recorded for only a single, recent generation, ignoring intergenerational preconditions and historical conferment of opportunity. We use the detailed geography of relative deprivation (hardship) to demonstrate that different family groups today experience different intergenerational outcomes and that there is a distinct Great Britain-wide geography to these inequalities. We trace the evolution of these inequalities back in time by coupling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Issues of ethnicity underpin our understanding of population diversity and the regional patterning of population characteristics in the wake of recent and historic waves of migration. Elsewhere (Longley et al 2021) we have argued that regional origins in ‘Old World’ countries have enduring inter-generational consequences for social mobility outcomes, and one of our motivations for improving the efficacy of names-based classification is to describe and evaluate the relative social circumstances of citizens who can trace their origins through any of a succession of waves of migration to the UK. As such, the creation of Onomap3 has several methodological and substantive touchpoints with research previously reported in this journal, as well as for regional science investigations more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Issues of ethnicity underpin our understanding of population diversity and the regional patterning of population characteristics in the wake of recent and historic waves of migration. Elsewhere (Longley et al 2021) we have argued that regional origins in ‘Old World’ countries have enduring inter-generational consequences for social mobility outcomes, and one of our motivations for improving the efficacy of names-based classification is to describe and evaluate the relative social circumstances of citizens who can trace their origins through any of a succession of waves of migration to the UK. As such, the creation of Onomap3 has several methodological and substantive touchpoints with research previously reported in this journal, as well as for regional science investigations more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Our chosen measure of social inequality is the Index of Multiple Deprivation (IMD: Ministry of Housing, Communities, & Local Government, 2019), published at Lower layer Super Output Area (LSOA, typically 1500 residents) scale or equivalent (Data Zones in Scotland, typically 784 residents). We reconcile the 2019 scores for England and Wales with 2020 scores for Scotland by assuming the index scores are broadly comparable (see also Longley et al, 2021): although differing in detail, the national measures for constituent UK countries are broadly comparable with respect to physical and social conditions such as income, employment, health, education, crime, barriers to housing and general living environment. As such, they are akin to ‘permanent income’ measures (Clark & Moore, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that these inequalities are formed and shaped by both long‐term and short‐term processes. Differences amongst long‐established British family groups, for instance, are overlain by geographic factors (Longley et al, 2021), while the Covid‐19 pandemic has been shown further to exacerbate socio‐economic inequalities between ethnic groups (see, for example, Nafilyan et al, 2021). In this paper we analyse population‐wide inequalities of outcome at the level of the individual and family group with respect to ancestral geographic origin, ethnic group, and probable country of origin.…”
Section: Introductionmentioning
confidence: 99%
“…PGS for educational attainment reflect that structure more than most traits (Haworth et al., 2019). In other words, people are not randomized across geography; instead, there are long‐running intergenerational patterns to social mobility, with many families effectively trapped in geographic areas of greater social deprivation (Longley et al., 2021), and the ability to migrate in part influenced by heritable phenotypes (e.g., health status, Brimblecombe et al., 2000). These considerations highlight a central challenge to identifying genetic causes of behavioral traits, the immense difficulty of disentangling population stratification from biological and social effects.…”
Section: The Backdropmentioning
confidence: 99%